Amp-PCR: combining a random unbiased Phi29-amplification with a specific real-time PCR, performed in one tube to increase PCR sensitivity. - Lena Erlandsson; Lars Peter Nielsen; Anders Fomsgaard (PLoS ONE, 2010)
In clinical situations where a diagnostic real-time PCR assay is not sensitive enough, leading to low or falsely negative results, or where detection earlier in a disease progression would benefit the patient, an unbiased pre-amplification prior to the real-time PCR could be beneficial. In Amp-PCR, an unbiased random Phi29 pre-amplification is combined with a specific real-time PCR reaction. The two reactions are separated physically by a wax-layer (AmpliWax®) and are run in sequel in the same sealed tube. Amp-PCR can increase the specific PCR signal at least 100×10(6)-fold and make it possible to detect positive samples normally under the detection limit of the specific real-time PCR. The risk of contamination is eliminated and Amp-PCR could replace nested-PCR in situations where increased sensitivity is needed e.g. in routine PCR diagnostic analysis. We show Amp-PCR to work on clinical samples containing circular and linear viral dsDNA genomes, but can work well on DNA of any origin, both from non-cellular (virus) and cellular sources (bacteria, archae, eukaryotes).